She Left the Party: College Students’ Meanings of Sexual Consent - Groggel, Anne (Violence against women, 2021)
At a moment when college sexual assault is described as an epidemic, it is important to understand college students’ implicit meanings of consent. Through 83 interviews, we examine students’ interpretations of a vignette in which neither character asked nor gave consent to sex. Gendered expectations significantly shaped whether students interpreted the male or female character as giving consent. When considering how students indicate interest in kissing or having sex, students interpreted acts such as leaving a party as indications of a man’s sexual interest and a woman’s willingness. That is, college students “expected” and employed implicit, gendered readings of actions that inform their understandings of implicit consent.